Motivasi Terselubung Gerakan Politik dan Fundamentalis terhadap Muslim - Indra Harahap; Rhabliani Matondang (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
This study analyzes the roots of fundamentalist Islamic political movements in the modern era by specifically exploring the logic in Islamic theology that is specific to Islamic fundamentalists. On that basis, this research attempts to critically dissect how Armstrong perceives Islamic fundamentalist political ideology. The Islamic fundamentalist movement, in particular, must be understood as a political movement. With this assumption, the position of the fundamentalists and the way they struggle and the ideological basis can be seen clearly. Based on the above themes, this study concludes two important findings: first, many forms of what is called "fundamentalism" essentially have to be seen as discourses of political theology, namely forms of nationalism or ethnicity, which are articulated religiously. Thus, fundamentalism can be understood as a political movement with an Islamic ideology. Second, psychologically, it is necessary to recognize that both the theology and ideology of fundamentalists are rooted in this fear starting with their insecurities that the secularists will eliminate them. It should also be realized that the fundamentalist movement is not an ancient movement or from the past, but is fundamentally modern and highly innovative. Keywords: political theology, fundamentalist Islam.